ULTRASONIC DUPLEX SCANNING AND CLINICAL PECULIARITIES OF THE EXTRACRANIAL ABNORMALITIES OF THE INTERNAL CAROTID ARTERIS IN CHILDREN - M.F. Abramova; N.S. Shurupova (Педиатрическая фармакология)
The analysis of 3380 cases laid the ground for describing the ultrasonic parameters of duplex scanning of brachiocephalic vessels in children suffering from various body and walking abnormalities. Clinical peculiarities of pathological deformations of the internal carotid artery at children are revealed. Prevalence of hemodynamically significant abnormalities of brachiocephalic vessels at males (85 percents of patients) is revealed. We offer modified classification of pathological tortuosities of the internal carotid artery at children [1–7].Key words: ultrasonic duplex scanning, brachiocephalic artery anomalies, cerebrovascular disease.